4. A COMPREHENSIVE ANALYSIS OF MEDICATION ADHERENCE IN OUTPATIENTS WITH HYPERTENSION IN VIET NAM (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the medication adherence rate for hypertension treatment in Vietnam and to investigate the associated factors.Research methods: A search was conducted from January 2023 to August 2024 across 26 Vietnamese articles from 3 regions of Vietnam.Results: Analysis revealed a medication adherence rate of 62% (95%CI: 0.54-0.70) among hypertensive patients. Adherence rates were 61% in the North, 59% in the Central region, and 65% in the South. Regarding gender, men exhibited a lower adherence rate of 48% compared to 56% for women. The compliance rate of patients in urban areas (76%) is higher than in rural areas (67%). Patients with a disease duration of more than 5 years had lower medication adherence (70%) than the group with a disease duration of 5 years or less (77%).Conclusions: The medication compliance rate of people with hypertension in Vietnam is relatively high. Region, age, gender, patient's place of residence, and duration of hypertension are factors related to medication compliance.
Keywords: Medication adherence; hypertension; Morisky scale (MMAS-8)